2020
DOI: 10.1017/jog.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

Over-winter persistence of supraglacial lakes on the Greenland Ice Sheet: results and insights from a new model

Abstract: We present a newly developed 1-D numerical energy-balance and phase transition supraglacial lake model: GlacierLake. GlacierLake incorporates snowfall, in situ snow and ice melt, incoming water from the surrounding catchment, ice lid formation, basal freeze-up and thermal stratification. Snow cover and temperature are varied to test lake development through winter and the maximum lid thickness is recorded. Average wintertime temperatures of −2 to $-30^{\circ }{\rm C}$ and total snowfall of 0 to 3.45 m lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…We used a simple 1D heat diffusion model adapted from ( 66 ) to investigate temperature evolution in the region of Anomaly-208 with a vertical resolution of 0.5 m under (i) no heat inputs or sinks and (ii) heat inputs and sinks prescribed manually as square waves to maintain the anomaly at a steady state. The energy input and sink required to sustain the anomaly can be used to estimate the deformation rate.…”
Section: Methodsmentioning
confidence: 99%
“…We used a simple 1D heat diffusion model adapted from ( 66 ) to investigate temperature evolution in the region of Anomaly-208 with a vertical resolution of 0.5 m under (i) no heat inputs or sinks and (ii) heat inputs and sinks prescribed manually as square waves to maintain the anomaly at a steady state. The energy input and sink required to sustain the anomaly can be used to estimate the deformation rate.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis suggests that increasing air temperatures, which contribute to increased summer melt, will likely lead to an increase in the number and area of buried lakes and therefore an increased volume of liquid water that is stored beneath the surface during the winter. Surface lake distribution across the GrIS has expanded inland to higher elevations (Howat et al, 2013), and it is expected that surface lakes will continue to form at higher elevations as air temperatures continue to rise in the future (Leeson et al, 2015). Thus, we also expect that buried lakes will form further inland at higher elevations in a warming climate, with potential implications for changing surface hydrology and total ice loss.…”
Section: Climate Drivers Of Buried Lake Distributionmentioning
confidence: 99%
“…This causes a significant reduction in surface scattering, and hence, the HH-HV difference can no longer distinguish between the frozen lake water and the surrounding glacier ice. However, lakes with a water depth from several meters up to tens of meters (which is the case for many SGLs; see [17,27,[40][41][42]) have a heat capacity which allows them to stay liquid over the whole winter if they are well isolated by a significant layer of ice and snow [19].…”
Section: Time Seriesmentioning
confidence: 99%
“…However, when a lake freezes over and is covered by fresh snow, it cannot be identified any longer, but this does not necessarily mean that the lake has disappeared. Energy-balance and phase transition modeling demonstrated that under the climatic conditions on the GrIS, ice lids form up to a thickness of~1-3 m, but below that depth, the water stays liquid [19].…”
Section: Introductionmentioning
confidence: 99%